Advances in Information and Communication Networks Proceedings of the 2018 Future of Information and Communication Conference (FICC), Vol. 1 - Arai, Kohei; Kapoor, Supriya; Bhatia, Rahul; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book, gathering the proceedings of the Future of Information and Communication Conference (FICC) 2018, is a remarkable collection of chapters covering a wide range of topics in areas of information and communication technologies and their applications to the real world. It includes 104 papers and posters by pioneering academic researchers, scientists, industrial engineers, and students from all around the world, which contribute to our understanding of relevant trends of current research on communication, data science, ambient intelligence, networking, computing, security and Internet of Things. This book collects state of the art chapters on all aspects of information science and communication technologies, from classical to intelligent, and covers both theory and applications of the latest technologies and methodologies. Presenting state-of-the-art intelligent methods and techniques for solving real-world problems along with a vision of the future research, this book is an interesting and useful resource.
End to End Deep Neural Network Frequency Demodulation of Speech Signals -- Performance Enhancement of MIMO - MGSTC using a New Detection and Decoding Technique -- A Novel Distributed Multi-Access Platform for Broadband Triple-Play Service Delivery -- Cognitive Channel Decoding -- Scenario-based Functional Safety for Automated Driving on the Example of Valet Parking -- Fair Comparison of DSS Codes -- Comparative Analysis of Digital Circuits using 16nm FinFET and HKMG PTM Models -- Possibilities to Improve Online Mental Health Treatment: Recommendations for Future Research and Developments -- Multi-Sensors 3D Fusion in the Presence of Sensor Biases -- 3D Circular Embedded Antenna Mounted on Coaxial Feeding for Future Wideband Applications.
Keywords: Computational intelligence; Telecommunication; Computational Intelligence; Communications Engineering, Networks